2010
DOI: 10.1007/s11207-010-9664-7
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of the Solar Limb: Models and Observations

Abstract: In this paper we compare observed, empirical, and modelled solar limb profiles and discuss their potential use to derive physical properties of the solar atmosphere. The PHOENIX, SolMod3D, and COSI radiative transfer codes as well as VAL-C models are used to calculate the solar limb shape under different assumptions. The main properties of each model are shown. The predicted limb shape as a function of wavelength for different features on the solar disk, such as quiet Sun, sunspots, and faculae, is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
6
29
0
Order By: Relevance
“…Rutten and Kostik, 1982;Shchukina and Trujillo Bueno, 2001). The spectrum of the quiet Sun calculated with COSI is in good agreement with the solar spectrum measured by SOLSTICE (up to 320 nm) and SIM (above 320 nm) onboard the SORCE satellite during the 2008 solar minimum, and with the SOLSPEC measurements during the ATLAS 3 mission in 1994 (Thuillier et al, 2011). Shapiro et al (2013a) showed that COSI can accurately reproduce the center-to-limb variation of solar brightness in the Herzberg continuum retrieved from the analysis of solar eclipses observed by LYRA/PROBA2 (Large Yield RAdiometer/PRoject for On-Board Autonomy).…”
Section: Cosisupporting
confidence: 76%
“…Rutten and Kostik, 1982;Shchukina and Trujillo Bueno, 2001). The spectrum of the quiet Sun calculated with COSI is in good agreement with the solar spectrum measured by SOLSTICE (up to 320 nm) and SIM (above 320 nm) onboard the SORCE satellite during the 2008 solar minimum, and with the SOLSPEC measurements during the ATLAS 3 mission in 1994 (Thuillier et al, 2011). Shapiro et al (2013a) showed that COSI can accurately reproduce the center-to-limb variation of solar brightness in the Herzberg continuum retrieved from the analysis of solar eclipses observed by LYRA/PROBA2 (Large Yield RAdiometer/PRoject for On-Board Autonomy).…”
Section: Cosisupporting
confidence: 76%
“…A study of the shape of the solar limb (models and observations) was carried out by Thuillier et al (2011). Several kinds of solar atmosphere models were compared.…”
Section: Spectral Dependence Of Solar Continuum Radiusmentioning
confidence: 99%
“…According to solar astrolabe measurement, the variation of the solar radius with solar activity is about 200 mas , and, according to physical solar models, the dependency to wavelength is about 20-30 mas (Thuillier et al 2011). Therefore, to validate these dependencies, especially the dependency to wavelength, one of the requirements is to have results without the effect of the processing method.…”
Section: Resultsmentioning
confidence: 99%